WAYANG KULIT SEBUAH TEATER BONEKA BALI - I Made Sudana (LP2M ISBI Bandung, 2018)
Wayang kulit Bali are one of the Balinese puppet art forms that still survive today. This art has undergone innovation according to the times. Among the striking forms of innovation in the field of music accompaniment, which originally used 4 pieces of gender wayang or gamelan bebatelan, but now accompanied by gamelan semar pagulingan or gamelan balaganjur which is a middle class bali music ensemble. Besides that, presenting vocal is the dalang, but now it has been added to the accompaniment of gerongan, namely the choir of a group of female singers and wra suara.